Final answer:
To solve the given system of equations using substitution, we set the two expressions for y equal to each other, solve for x, which is -2, and then substitute the value of x back into one of the original equations to find y, which is 6.
Step-by-step explanation:
To solve the system of equations using substitution, we will substitute one equation into the other. We have the system:
Since both equations equal y, we can set them equal to each other:
2x + 10 = x + 8
Now, we can solve for x:
- Subtract x from both sides: 2x - x + 10 = 8
- Simplify: x + 10 = 8
- Subtract 10 from both sides: x = -2
Now, substitute x back into one of the original equations to find y:
y = 2(-2) + 10 = -4 + 10 = 6
So the solution to the system of equations is x = -2 and y = 6.